Economic empowerment of the PKK group through starfruit kombucha functional food innovation in Kepanjenlor, Blitar - Juwita, Ratna; Manggara, Algafari Bakti; Mizar, Muhammad Alfian; Chayara, Almira Syaqila Mayndie; Zahra, Shakila Aliya; Hafidz, Abdullah Syamil Hanafi; Gunawan, Pristiko (Community Empowerment, 2025)
Starfruit is a primary commodity in Kepanjenlor Village, Blitar Regency, yet its utilization remains suboptimal as it is predominantly sold in its fresh form. This situation results in a harvest surplus that drives down market prices. This community service project aims to introduce functional food innovation by transforming starfruit into kombucha tea for local PKK (Family Welfare Movement) members to enhance its economic value. The methods employed include technical training, mentoring, as well as monitoring and evaluation. The results demonstrated a significant 75% increase in participants' skills in processing starfruit into kombucha. Additionally, 95% of participants expressed a strong interest in producing and marketing the product independently and demonstrated a clear understanding of its health benefits. This program successfully strengthened the entrepreneurial capacity of the PKK members by leveraging local potential through functional food innovation.